Simultaneous Analysis of Two Phytohormones in Chili and Wheat Using HPLC Using Novel Calixarene as SPE Sorbent. (27th October 2016) - Chen, Yanlong; Yang, Liu; Zhang, Wenfen; Deng, Zhifen; Wang, Fei; Li, Yue; Meng, Lei; Wu, Ningpeng; Ban, Fuguo; Zhang, Shusheng
Abstract: In this paper, a high-performance liquid chromatography with ultraviolet (HPLC-UV) detection method, using tetraazacalix[2]arene[2]triazine-modified silica gel (NCS) as solid-phase extraction (SPE) sorbent, was developed for extracting and purifying the two phytohormones (indole-3-acetic acid (IAA) and indole-3-butyric acid (IBA)) in chili and wheat samples from different organs of chili and wheat. The limits of detection were about 0.02 and 0.04 μg/mL, and the limits of quantification were 0.04 and 0.20 μg/mL for IAA and IBA, respectively. The intraday and interday RSDs ( n = 6) of peak areas and retention times were in the range of 0.76–1.20%. In addition, overall recoveries through the extraction and NCS–SPE purification ranged from 78.4% to 86.8% for IAA and IBA were obtained. Compared with the commercial SPE sorbents, NCS featured excellent selectivity to retain IAA and IBA in the sample matrices. In addition, the results more clearly indicated that high IAA and IBA content existed in roots and leaves of wheat and chili; in other organs of the plants, the concentration of the two phytohormones is lower. The results from theoretical computation were consistent with the retention behaviors of IAA and IBA on NCS. The proposed NCS–SPE–HPLC method is highly effective for trace analysis of the two phytohormones in plant samples.